Laki-Laki dan Perempuan dalam Bingkai Struktur: Isu Gender dalam Film Billy Elliot - Andina Dian Dwi Fatma (Atma Jaya Indonesia Catholic University, Jakarta, 2012)
The patriarchy structure has been famously known as favorable to the male. However, to what extent do men enjoy this superiority? This article argued that men are not always able to position themselves successfully in the construction of a system called ‘masculinity’. Both men and women are just performing the role expected of them. So it is extremely important for them to negotiate, and renegotiate, their roles and positions in society. That way, both men and women will be able to feed their existence, above and beyond structure.